Valley and spin quantum Hall conductance of silicene coupled to a ferroelectric layer - Rafi-Ul-Islam, S. M.; Siu, Zhuo Bin; Sahin, Haydar; Jalil, Mansoor B. A. (Frontiers in Physics, 2022)
We study the quantum valley and Hall conductances in silicene coupled to a ferroelectric (FE) layer. The spin orbit interaction in silicene couples the valley, pseudospin and real spin degrees of freedom resulting in a topological Berry curvature in the system. The finite Berry curvature in turn induces a transverse Hall conductance. In particular, if the Fermi level Ef is within the bulk energy gap, the Hall conductance is quantized to integer multiples of π. We study the quantum spin and valley Hall conductivities (QSH and QVH) as a function of the applied out-of-plane electric field for different values of Ef and temperature. Both conductivities vary linearly with 1/|Ef | when Ef is within the conduction or valence bands but reaches a quantized plateau value when Ef is within the bulk gap. Further, by coupling silicene to a FE layer, the QSH and QVH signals can be modulated by means of the coupling strength. This can potentially provide a robust topological memory read-out with distinct binary outputs over a wide temperature range.